Can topical lignocaine reduce behavioural response to heel prick?. Issue 1 (January 1995) - Rushforth, J. A.; Griffiths, G.; Thorpe, H.; Levene, M. I.
Abstract : In a randomised, double blind, controlled study the ability of 5% lignocaine ointment to reduce the behavioural response to heel lance in 30 healthy neonates was assessed. Five per cent lignocaine ointment applied to the heel under an occlusive dressing for one hour before heel prick did not reduce the infants' behavioural response to the heel prick procedure.